2014
DOI: 10.1016/j.foreco.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of traditional forest management in southern Moravia: A history of the past 700 years

Abstract: European broadleaved forests have been influenced by humans for centuries. Historical management practices are related to environmental conditions but the role of socio-economic factors is also important. For the successful restoration of traditional management for conservation purposes, detailed knowledge on management history and on the driving forces of historical forest changes is necessary. In order to reconstruct long-term spatio-temporal dynamics in forest management, we chose the Pálava Protected Lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 41 publications
2
62
0
1
Order By: Relevance
“…Coppice management was widespread throughout European forests for centuries but was largely abandoned in the second half of the 19 th century (Mullerova et al 2014, Srámeki et al 2015, mostly due to the substitution of firewood with fossil fuels (Sieferle 2001) and changes in silvicultural practices (Rackham 2008). In Turkey, coppicing has been a common practice for hundreds of years .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coppice management was widespread throughout European forests for centuries but was largely abandoned in the second half of the 19 th century (Mullerova et al 2014, Srámeki et al 2015, mostly due to the substitution of firewood with fossil fuels (Sieferle 2001) and changes in silvicultural practices (Rackham 2008). In Turkey, coppicing has been a common practice for hundreds of years .…”
Section: Introductionmentioning
confidence: 99%
“…Because it favors vegetative regeneration, coppice management can also result in low genetic diversity of the stands (Calikoglu & Kavgaci 2002). Nonetheless, coppicing is still commonly used as a forest management system in southeastern Europe (Mullerova et al 2014). In addition, there has been a renewed interest in utilizing coppicing as a tool for biomass production and nature conservation (Srámeki et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In faggete gestite della Danimarca, Aude & Poulsen (2000) hanno rilevato l'assenza di molte crittogame epifite rispetto a faggete lasciate alla libera evoluzione. Al contrario, la mancanza di gestione dei boschi può avere effetti negativi sulla gestione e sul controllo degli attacchi parassitari, sulla biodiversità delle specie arboree che compongono il soprassuolo (Zlatanov et al 2012) e sulla biodiversità a livello di paesaggio (Müllerová et al 2014). Pertanto, se l'abbandono colturale ha effetti negativi sulla produzione legnosa, sulla protezione idrogeologica e sulla ricreazione in foresta, può avere, almeno parzialmente, un effetto positivo in termini di biodiversità specifica.…”
Section: Fattore DI Minacciaunclassified
“…Those landscapes have been created by long-term application of traditional landuse techniques, coppicing and pollarding in forestry belongs among them. Coppicing (Stajic at al., 2009;Szabo, 2009;Sjölund & Jump, 2013, Müllerová et al, 2014Szabó et al, 2015) and pollarding (Rozas, 2004;Read, 2006;Cousins & Duval, 2012;Mitchell, 1989) were widespread in Europe until the beginning of the 20 th century (Szabó et al, 2015). Dendroarchaeological research showed that coppicing started in the Neolithic, and was practiced throughout the European history (Szabo, 2009).…”
Section: Introductionmentioning
confidence: 99%